Scanning electron microscope study of Saccharomyces cerevisiae spheroplast formation. - Pringle, A T (1979)
A suspension of Saccharomyces cerevisiae NCY366 in buffered 1.2 M sorbitol containing Zymolyase-5000 (a beta-glucanase-containing preparation/showed maximum osmotic sensitivity after 30 min of incubation at 30 degrees C. A scanning electron microscope study of spheroplast formation, using a very high resolution (4-nm) machine, revealed several new morphological features. The surface of the plug in bud scars on intact cells appeared warty. The wall, which assumed a beady appearance as digestion proceded, ultimately sloughed off to reveal the furrowed surface of the plasma membrane. Bud scars were resistant to digestion and. as incubation proceeded, they became surrounded by an outer annulus, which may be the seconary septum. Wall material was completely removed from the majority of cells only after 60 min of digestion. The surface of spheroplasts was studded with particles, about 25 to 30 nm in diameter. Many spheroplasts had a single large indentation, which may be in that part of the plasma membrane originally underlying the birth scar.